P–318 Short (seven days) versus conventional (fourteen days) estrogen priming in an artificial frozen embryo transfer cycle: a randomised controlled trial. (6th August 2021) - Racca, A; Santos-Ribeiro, S; Panagiotis, D; Boudry, L; Mackens, S; Vos, M D; Tournaye, H; Blockeel, C
Abstract: Study question: What is the impact of seven days versus fourteen days' estrogen (E2) priming on the clinical outcome of frozen-embryo-transfer in artificially prepared endometrium (FET-HRT) cycles? Summary answer: No significant difference in clinical/ongoing pregnancy rate was observed when comparing 7 versus 14 days of estrogen priming before starting progesterone (P) supplementation. What is known already: One (effective) method for endometrial preparation prior to frozen embryo transfer is hormone replacement therapy (HRT), a sequential regimen with E2 and P, which aims to mimic the endocrine exposure of the endometrium in a physiological cycle. The average duration of E2 supplementation is generally 12–14 days, however, this protocol has been arbitrarily chosen whereas, the optimal duration of E2 implementation remains unknown. Study design, size, duration: This is a single-center, randomized, controlled, open-label pilot study. All FET-HRT cycles were performed in a tertiary centre between October 2018 and December 2020. Overall, 150 patients were randomized of whom 132 were included in the analysis after screening failure and drop-out. Participants/materials, setting, methods: The included patients were randomized into one of 2 groups; group A (7 days of E2 prior to P supplementation) and group B (14 days of E2 prior to P supplementation). Both groups received blastocyst stage embryos for transfer on the 6th day of vaginal P administration. Pregnancy was assessed by an hCG blood test 12 days after FET and clinical pregnancy was confirmed by transvaginal ultrasound at 7 weeks of gestation. Main results and the role of chance: Following the exclusion of drop-outs and screening failures, 132 patients were finally included both in group A (69 patients) or group B (63 patients). Demographic characteristics for both groups were comparable. The positive pregnancy rate was 46.4% and 53.9%, (p 0.462) for group A and group B, respectively. With regard to the clinical pregnancy rate at 7 weeks, no statistically significant difference was observed (36.2% vs 36.5% for group A and group B, respectively, p = 0.499). The secondary outcomes of the study (biochemical pregnancy, miscarriage and live birth rate) were also comparable between the two arms for both PP and ITT analysis. Multivariable logistic regression showed that the HRT scheme is not associated with pregnancy rate, however, the P value on the day of ET is significantly associated with the pregnancy outcome. Limitations, reasons for caution: This study was designed as a proof of principle trial with a limited study population and therefore underpowered to determine the superiority of one intervention over another. Instead, the purpose of the present study was to explore trends in outcome differences and to allow us to safely design larger RCTs. Wider implications of the findings: The results of this study give the confidence to perform larger-scale RCTs to confirm whether a FET-HRT can be performed safely in a shorter time frame, thus, reducing the TTP, while maintaining comparable pregnancy and live birth rates. Trial registration number: NCT03930706